1997
DOI: 10.1029/97wr01619
|View full text |Cite
|
Sign up to set email alerts
|

The minimum structure solution to the inverse problem

Abstract: where the superscript T means matrix transpose. For the sake of generality, in order to account for nonuniform magnitudes and tendencies for simultaneous change (i.e., correlation) in the observation errors, a weighted least squares approach is adopted min (y-h(s))rR-•(y-h(s))where R is an n by n positive definite matrix. Such least squares formulations to the inverse problem are quite popular. One of the earliest applications was given by Jahns [1966]. In groundwater hydrology a well-known approach is the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Furthermore, it originally required that the flow equations could be linearized (small variance assumption). Only in recent years was this approach extended to quasilinear and even nonlinear problems (e.g., see Kitanidis, 1995Kitanidis, , 1997Kitanidis, , 1998Kitanidis, , 1999.…”
Section: Cokrigingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it originally required that the flow equations could be linearized (small variance assumption). Only in recent years was this approach extended to quasilinear and even nonlinear problems (e.g., see Kitanidis, 1995Kitanidis, , 1997Kitanidis, , 1998Kitanidis, , 1999.…”
Section: Cokrigingmentioning
confidence: 99%
“…One can examine two limiting cases: in the case where the range of the a priori covariance is very wide, a differential second-order operator comparable to equation 15 intervenes in the regularization term; contrariwise, if the range is so small that the a priori errors over two neighboring meshes are not correlated, the effect, in the absence of log-transmissivity data, is equivalent to a regularization that minimizes the quadratic mean of the log-transmissivities. In hydrogeology, Kitanidis (1997) explored the relation between the geostatistical approach and the so-called Backus-Gilbert smallest solution, and generalized the flatness criterion for one, two, or three dimensions (Kitanidis, 1999).…”
Section: Robustness Regularization and The Cauchy Problemmentioning
confidence: 99%
“…In subsurface hydrology, however, the geostatistical framework is more common. Kitanidis (1997) and independently Maurer et al (1998) showed that the two approaches are mathematically equivalent to each other.…”
Section: Erdal and O A Cirpka: Joint Inference Of Recharge And Cmentioning
confidence: 99%
“…These methods, usually based on gradient minimization, have been described in the literature. 2 Automated history matching has seen good success in single-phase problems and in matching pressure. However, because of the large number of equations involved in a field-scale problem, the non-linear properties of flow parameters, and the subjective nature of 'matching,' automatic techniques have found limited practical application.…”
Section: Introductionmentioning
confidence: 99%